Effectiveness of Integrated and Comprehensive Geriatric Care Program of Ministry of Health on Physical and Mental Health of Older Adults in Golestan Province - Mahin Sadat Azimi; Fatemeh Arab Ameri; Mohammad Reza Honarvar; Neda Sadat Nazaripanah; Yadollah Abolfathi Momtaz; Elham Lotfalinezhad (University of Social Welfare & Rehabilitation Sciences, 2021)
Objectives: In order to maintain and improve older adults' health, the integrated and comprehensive geriatric care program has been developed and run by ministry of health. The present study was conducted to evaluate the effectiveness of this program on physical and mental health of older adults in Golestan province in 2019. Methods & Materials: The present retrospective cohort study employed a multistage clustered random sampling technique to obtain 500 e-health records of older adults during 2017-2019. The data on blood pressure, depression, and BMI were extracted from e-health records. Data analysis was conducted using repeated measure anova, paired t-test and Wilcoxon tests. The SPSS statistics software v. 20 was used to perform data analysis Results: Of the 500 cases studied, were male and female, respectively. The Mean±SD age of the participants was 69.97±7.45 years. The results of inferential statistics showed that the mean score of systolic blood pressure was significantly decreased through study period (P<0.001). However, through study period depression score was significantly increased (P≤0.05). There was no significant difference in BMI index. Conclusion: The results of this study showed that the integrated and comprehensive geriatric program was effective for controlling blood pressure, however was not effective for preventing depression. Therefore, stakeholders should pay more attention towards establishing appropriate program to improve older adults' mental health.